Carboxylation of multiwalled carbon nanotube attenuated the cytotoxicity by limiting the oxidative stress initiated cell membrane integrity damage, cell cycle arrestment, and death receptor mediated apoptotic pathway. Issue 8 (25th February 2015) - Liu, Zhenbao; Liu, Yanfei; Peng, Dongming
Abstract In this study, the effects of carboxylated multiwalled carbon nanotubes (MWCNTs‐COOH) on human normal liver cell line L02 was compared with that of pristine multiwalled carbon nanotubes (p‐MWCNTs). It was shown that compared with MWCNTs‐COOH, p‐MWCNTs induced apoptosis, reduced the level of intracellular antioxidant glutathione more significantly, and caused severer cell membrane damage as demonstrated by lactate dehydrogenase leakage. Cell cycles were arrested by both MWCNTs, while p‐MWCNTs induced higher ratio of G0/G1 phase arrestment as compared with MWCNTs‐COOH. Caspase‐8 was also activated after both MWCNTs exposure, indicating extrinsic apoptotic pathway was involved in the apoptosis induced by MWCNTs exposure, more importantly, MWCNTs‐COOH significantly reduced the activation of caspase‐8 as compared with p‐MWCNTs. All these results suggested that MWCNTs‐COOH might be safer for in vivo application as compared with p‐MWCNTs. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 2770–2777, 2015.